Profile of Suaitabilit of BPJS Patient Drug Prescription With The National Formularium at Juata Community Health Center During The Periode of May-July 2024 - Arny_, arnny pertiwi sari; Sari Wijayanti; Jufri Ubrusun (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Compliance with the National Formulary not only improves the quality of health services in primary health facilities but also ensures the efficiency of treatment costs and the fulfillment of the right and safe drug needs for the community. This study supports efforts to strengthen the implementation of the National Formulary as a strategic guideline to increase access to quality health services, improve pharmaceutical governance, and encourage efficiency of the health budget. Objective: This study aims to assess the suitability of drug prescriptions for patients registered in the BPJS Kesehatan program in accordance with the National Formulary (Fornas) at the Juata Health Center during the period May to July 2024. Research Methods: The research design applied was non-experimental with a retrospective descriptive approach. A total of 300 BPJS patient prescriptions were selected as samples from a total population of 8704 prescriptions using the Slovin method with a precision level of 90%. Data were analyzed descriptively to calculate the percentage of prescription suitability based on prescription sheets and drug items. Results: The results showed that the suitability of prescriptions based on prescription forms and drug items reached 100% during the study period. Of the total 101 prescribed drug items (28 items in May, 41 items in June, and 32 items in July), all were based on the National Formulary. Conclusion: These results provide the conclusion that the Juata Health Center has met the standards of pharmaceutical services, with drug prescriptions that fully support rational, efficient, and effective drug use. The results of this study have significant relevance to national health policies, especially in the implementation of the National Health Insurance (JKN) program.